Analisis Media Monitoring Terhadap Brand Hamlin Pada Bulan Maret 2024 Menurut Teori Evring Goffman - Alifia Sherli Septyani; Hanny Hafiar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The fashion industry in 2024 will continue to develop along with developing trends, technology and consumer needs. The existence of the fashion industry as one of the largest industries in the world contributes to the Indonesian economy. In the Indonesian fashion industry, there are many local brands. One of them is the Hamlin brand. In mid-March 2024, Hamlin was hit by an issue of product counterfeiting. This issue prompted the author to carry out media monitoring to monitor and analyze updates related to conversations regarding the Hamlin brand, including specific, positive opinions and negative opinions that could affect the public's reputation and trust in the Hamlin brand. This research uses a descriptive qualitative approach. Research data was obtained from the results of analysis of reviews on several social media. Researchers also use secondary data in the form of journal articles, books and other literature on the internet. The theory used in this research is Erving Goffman's dramaturgical theory. The results of the analysis show that the issue of product counterfeiting involving the Hamlin Brand has significantly disrupted the brand's image and reputation. Hamlin Brand's ineffective response to this issue has exacerbated the situation and increased public doubt and distrust of the brand.